2014
DOI: 10.1002/bmc.3386
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive ultra‐high‐pressure liquid chromatography method for quantification of antichagasic benznidazole in plasma: application in a preclinical pharmacokinetic study

Abstract: Benznidazole (BNZ) and nifurtimox are the only drugs available for treating Chagas disease. In this work, we validated a bioanalytical method for the quantification of BNZ in plasma aimed at improving sensitivity and time of analysis compared with the assays already published. Furthermore, we demonstrated the application of the method in a preclinical pharmacokinetic study after administration of a single oral dose of BNZ in Wistar rats. A Waters® Acquity UHPLC system equipped with a UV-vis detector was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Workman et al reported a similar C max , 36 g/ml, in mice treated with 78 mg/kg of BNZ (12). In this study, the elimination half-life (t 1/2b ) of BNZ was 2.03 h, which is similar to the values reported by Davanço et al, Moreira da Silva et al, and Workman et al, which were 2.7, 1.6, and 1.6 h, respectively (12,16,18). These short half-lives indicate a high metabolism, which is responsible for low oral bioavailability.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Workman et al reported a similar C max , 36 g/ml, in mice treated with 78 mg/kg of BNZ (12). In this study, the elimination half-life (t 1/2b ) of BNZ was 2.03 h, which is similar to the values reported by Davanço et al, Moreira da Silva et al, and Workman et al, which were 2.7, 1.6, and 1.6 h, respectively (12,16,18). These short half-lives indicate a high metabolism, which is responsible for low oral bioavailability.…”
Section: Discussionsupporting
confidence: 89%
“…However, Morilla et al observed a BNZ t 1/2b of 3.5 h after intravenous administration (14). This result was not expected, because the t 1/2b of an orally administered drug should be longer than that of an intravenously administered one due to the absorption phase (18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The linear concentration range was 0.15 to 20 g/ml. These chromatographic conditions were used in previous studies of BNZ pharmacokinetics in rats (23).…”
Section: Methodsmentioning
confidence: 99%
“…18 Chromatography has been particularly important for drug quantification because of its very high sensibility and selectivity, 17 which has allowed this technique to be employed in the quantification of drugs isolated or in biological medium, but also to analyze the incorporation of drugs in nanocarriers as well as in release and stability studies. To the best of our knowledge, however, chromatographic methods for quantification of BZN in lipid nanostructures have not been developed yet.…”
Section: Introductionmentioning
confidence: 99%